Patients’ Satisfaction with Primary Health Care Centers’ Services, Majmaah, Kingdom of Saudi of Saudi Arabia - Mohamed, Elsadig Yousif; Mahmoud, Waqas Sami; Alotaibi, Abdullah; Alfarag, Abdulrahman; Almutairi, Ahmed; Alanzi, Fahad (International Journal of Health Sciences, 2015)
Background: PHC Patient’ satisfaction represents a key marker for the quality of health care delivery and this internationally accepted factor needs to be studied repeatedly for smooth functioning of the health care systems. The objectives of the current study were to determine the level of patients’ satisfaction with the primary health care services provided in Majmaah city, Kingdom of Saudi Arabia; to identify the reasons behind satisfaction or dissatisfaction and to determine the effect of the social factors on the level of satisfaction. Methodology: The study was a cross-sectional facility- based. The sample comprised 370 patients selected by stratified and systematic sampling at the health centers’ level and the patients’ level respectively. The data were collected by a pre-tested questionnaire and analyzed by SPSS software. Results: Patients’ level of satisfaction was 82%. The reasons behind satisfaction were cleanliness of the facilities and technical competencies of the staff (33.1% and 24.2%). The study showed that the most stated reason behind dissatisfaction was the unsuitable buildings (29%). Significant association was found between the level of patients’ satisfaction about PHC centers services and the respondents’ level of education. Conclusion: The level of satisfaction with the services provided by PHC centers in Majmaah is high. The gender, marital status and income have no effect on the level of satisfaction with the services provided by PHC centers. However, the lower educated are more satisfied than the higher educated. Cleanliness, competence of the staff along with respect and good handling are the drivers behind the high level of satisfaction. Kew words: Patients, Satisfaction, Primary health care centers.